Intimate citizenship and gendered well-being: the claims and interventions of women's movements in Europe - Roseneil, Sasha (2011)
Over the past 40 years women’s movements have expanded the scope of the politics of well-being, bringing issues of intimate life into the realm of claims for citizenship. In using the concept of ‘intimate citizenship’, we are incorporating the central second wave feminist claim that ‘the personal is political’, that ‘public’ and ‘private’ are always mutually entangled. We draw, in particular, on the work of Ken Plummer (2003) who has developed the concept of intimate citizenship in preference to the rather narrower notion of sexual citizenship which has been used by a number of other sociologists (for instance, Evans 1993, Weeks 1998, Bell and Binnie 2000, Richardson 2000). Plummer suggests that the ‘intimate citizenship project’ looks at ‘the decisions people have to make over the control (or not) over one’s body, feelings, relationships; access (or not) to representations, relationships, public spaces, etc; and socially grounded choices (or not) about identities, gender experience; erotic experiences’ (1995: 151, original emphasis). It refers to the fact that, in the wake of the movements for gender and sexual equality and change, ‘our intimacies are now thoroughly contested’ (2003: 13). This means both that the realm of personal life and close relationships is an arena of public, politicized struggle to change law, policy and culture, and that, as individuals, we face a ‘growing array of “choices” in our personal life … concerning families, gender, bodies, identities and sexualities’ (2003: 4).